Implementation of NonLinear Controller with Anti-Windup on Xilinx FPGA - Ahmed, Samet; Yahia, Kourd; Dimitri, Lefebvre (Arabian Journal for Science and Engineering, 2024)
This article describes a research study on an electromechanical system with saturation, where a fuzzy hybrid controller with integral action and anti-windup is applied. The study focuses on implementing this Integral Fuzzy Logic Controller (IFLC) on a Field-Programmable Gate Array (FPGA) board. The fuzzy controllers, known for their effectiveness in handling disturbances and saturations, are used in a parallel structure. To optimize the performance of the controller, the Particle Swarm Optimization (PSO) technique is employed to tune the membership functions and feedback loop gains. The complex algebraic concepts and Type 1 fuzzy logic algorithms are transformed into mathematical equations suitable for VHSIC Hardware Description Language (VHDL). The proposed controller is co-simulated using Vivado and Xilinx® System Generator (XSG) tools on both software and hardware platforms. The utilization of fixed-point data propagation in the controller's structure ensures optimized implementation methods. The performance index of our controller surpasses that of a conventional Proportional-Integral-Derivative (PID) controller, demonstrating superior efficacy in regulating the system dynamics. To verify the efficacy of the proposed control strategy, a thorough comparison is done using control simulations between it and previous PID systems. The results show a 31% decrease in speed overshoot.